2016
DOI: 10.1016/j.marpetgeo.2016.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Deep-seated faults and hydrocarbon leakage in the Snøhvit Gas Field, Hammerfest Basin, Southwestern Barents Sea

Abstract: High-quality 3D seismic data are used to analyze the history of fault growth and hydrocarbon leakage in the Snøhvit Field, southwestern Barents Sea. The aim of this work is to evaluate the role of tectonic fracturing as a mechanism driving fluid-flow in the study area. To achieve this aim, an integrated approach including seismic interpretation, multiple seismic attribute analysis, fault modeling and displacement analysis was used.The six major faults in the study area are dip-slip normal faults which are char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 91 publications
1
39
0
Order By: Relevance
“…The Barents Sea Ice Sheet (BSIS) retreated in stages [50], leaving parts of the Barents Sea Shelf ice free, whilst other parts were still under an ice sheet. Lateral distribution of maximum horizontal stresses also could have resulted in horizontal and vertical migration of HCs, as well as structural inversion and fault reactivation over the greater Barents Sea area [17,33,80].…”
Section: Fault Controlled Hydrocarbon Leakagementioning
confidence: 99%
See 1 more Smart Citation
“…The Barents Sea Ice Sheet (BSIS) retreated in stages [50], leaving parts of the Barents Sea Shelf ice free, whilst other parts were still under an ice sheet. Lateral distribution of maximum horizontal stresses also could have resulted in horizontal and vertical migration of HCs, as well as structural inversion and fault reactivation over the greater Barents Sea area [17,33,80].…”
Section: Fault Controlled Hydrocarbon Leakagementioning
confidence: 99%
“…Past petroleum system modelling studies were coarse and first focused on the implementation of glacial cycles in 2D [10], followed by a 3D PSM study at a 2 km × 2 km scale grid resolution, where petroleum leakage was addressed explicitly by capillary leakage though seal failure. Moreover, recent studies of the Barents Sea revealed that the key regional faults (Figures 1 and 3) in the Hammerfest Basin, namely NS, SW-NE and NW-SE faults [13,17], play a key role in petroleum migration from deeper Jurassic reservoirs ( Figures 3 and 4) to the shallow stratigraphy and up to the seabed [16,17,30], resulting in pockmarks (Figures 4 and 5), inferred gas hydrates [30,31], amplitude anomalies, gas chimneys ( Figures 3 and 4) and shallow gas accumulations [16,30,32,33]. Evidence of condensate type light hydrocarbons charging the seabed sediments also indicate a deep origin of the fluids and present-day microseepage [34].…”
Section: Introductionmentioning
confidence: 99%
“…Pockmarks are also visible along the seabed creating local depressions which are recognized in the seismic section [8,28] (Figure 7). They are dominantly seen above the fault graben structure.…”
Section: Seismic Interpretationmentioning
confidence: 98%
“…The EI is the ratio of the footwall to hanging wall stratal thickness, where EI values > 1 represent thickening of the footwall. These measurements provide insight into the D r a f t 9 timing of fault activity and potential reactivation of faults by dip linkage as well as distinguish faults that develop through syn-sedimentary or blind propagation (Baudon and Cartwright 2008b;Robson et al 2016;Mohammedyasin 2015;Tvedt et al 2013). The T-z profile and EI were determined on individual faults by plotting the depths to the midpoint of the respective hanging wall and footwall cut-offs (Baudon and Cartwright 2008b;Mohammedyasin 2015).…”
Section: Seismic Datasets and Processingmentioning
confidence: 99%